2018
DOI: 10.1111/cjag.12190
|View full text |Cite
|
Sign up to set email alerts
|

Consumer purchase intentions for pork with enhanced carnosine–A functional food

Abstract: In this study, Canadian consumers’ preferences for enhanced carnosine (a naturally occurring dipeptide that exhibits antiaging properties) in pork are examined. Carnosine is a relatively unknown nutrient to the public such that we are interested in understanding the relative merits of informing consumers of enhanced carnosine levels through a possible health claim, a nutrient content claim or including it in the nutrition facts table (NFT). As a basis of comparison, we include two other possible labels, a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The influence of age on WTP is in line with the current literature, suggesting that younger people are interested in functional characteristics [88] and negative relations were found significant toward health and nutrition claim on the label [89].…”
Section: Discussionsupporting
confidence: 88%
“…The influence of age on WTP is in line with the current literature, suggesting that younger people are interested in functional characteristics [88] and negative relations were found significant toward health and nutrition claim on the label [89].…”
Section: Discussionsupporting
confidence: 88%
“…Following a large quantity of literature, which uses CBC experiments to estimate WTP for credence attributes of food (Ehmke et al , 2008; Barreiro-Hurle, Gracia and de-Magistris, 2010; Ortega et al , 2011; Wu et al , 2015b; Wu et al , 2015a; Ortega et al , 2016; Arenna et al , 2019), this methodology is utilized to investigate Chinese consumers’ valuation on attributes of interest regarding functional sausage products. The product profile of pork sausages in the current study is described by four attributes (one in the country of origin domain and three in the nutrition claim domain), in addition to the price factor (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Eqn (3) is unconditional, as the variance of random parameters βn, causes correlation in unobserved utility across alternatives. This allows consumers to have heterogenous preferences for pork sausages, as suggested by various studies on pork-related products (Barreiro-Hurle et al , 2010; Ortega et al , 2011, 2017; Wu et al , 2015b; Arenna et al , 2019), and affords further consumer segmentation according to preferences. When consumers are classified into M latent classes of homogeneous subjects, preference heterogeneity is only present between classes but not within classes.…”
Section: Methodsmentioning
confidence: 99%
“…Consumers tend to believe that food contributes to their health[ 5 ]. Goddard and Muringai[ 6 ] reported that consumers were willing to pay more for pork with enhanced carnosine levels. Chicken meat contains more anserine than other meats, such as beef and pork[ 7 ], making it a good source of IDPs.…”
Section: Introductionmentioning
confidence: 99%